The Media Welfare State - Hallvard Moe (University of Michigan Press, 2014)
The Media Welfare State: Nordic Media in the Digital Age is the first theoretically-driven book to comprehensively address the central dynamics of the digitalization of the media industry in the Nordic countries - Sweden, Norway, Denmark, Finland and Iceland - and the ways media organizations there are transforming to address the new digital environment. The authors address Nordic media-industry structure and content from the standpoint of scholarly perspectives on global, regional and local approaches to media development. Taking a comparative approach, they provide an overview of media institutions and policy throughout the region, focusing on the impact of Information and Communication Technology/Internet and digitalization on the Nordic media sector. As illustrations, the authors draw on a wide range of cases, including developments in media forms such as television, radio, the press and the public service media institution.